2012
DOI: 10.1080/03081079.2012.721662
|View full text |Cite
|
Sign up to set email alerts
|

Semi-automated knowledge discovery: identifying and profiling human trafficking

Abstract: We propose an iterative and human-centred knowledge discovery methodology based on formal concept analysis. The proposed approach recognizes the important role of the domain expert in mining real-world enterprise applications and makes use of specific domain knowledge, including human intelligence and domain-specific constraints. Our approach was empirically validated at the Amsterdam-Amstelland police to identify suspects and victims of human trafficking in 266,157 suspicious activity reports. Based on guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The findings on the nature and scope of the menace revealed that the Ghanaian situation was similar to the reported cases of human trafficking from many different parts of the world as reported by Shelley and Lee (2007), Kempadoo et al (2015), and US Department of State (2003). In many different parts of the world including New York (Nack, 2010), Netherlands (Poelmana et al, 2012), and Malaysia (Stanslas, 2010), the police service was engaged in multi-dimensional approaches to limit the scope of human trafficking but the findings from this study indicated that the government of Ghana and GPS had not put in much effort to limit the scope of human trafficking in Ghana as reported by Aning et al (2013).…”
Section: Offence Yearmentioning
confidence: 70%
See 1 more Smart Citation
“…The findings on the nature and scope of the menace revealed that the Ghanaian situation was similar to the reported cases of human trafficking from many different parts of the world as reported by Shelley and Lee (2007), Kempadoo et al (2015), and US Department of State (2003). In many different parts of the world including New York (Nack, 2010), Netherlands (Poelmana et al, 2012), and Malaysia (Stanslas, 2010), the police service was engaged in multi-dimensional approaches to limit the scope of human trafficking but the findings from this study indicated that the government of Ghana and GPS had not put in much effort to limit the scope of human trafficking in Ghana as reported by Aning et al (2013).…”
Section: Offence Yearmentioning
confidence: 70%
“…In some countries such as Australia, the police consider people smuggling as a threat to national security (Pickering, 2004). In Netherlands, the operational practice of the police uses human-centered approach to gather unstructured information that reveals many unknown human trafficking practices (Poelmana et al, 2012). In Malaysia, the major human trafficking problem confronting the police concerns trans-border security that prompted the police to strengthen their maritime governance to control the influx of illegals to curtail public corruption fueled by human trafficking (Stanslas, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In [21], authors have investigated a problem of human trafficking, which requires detection and interpretability, so they applied used Formal Concept Analysis. In [4], authors also have investigated this algorithm, but for specific sequences.…”
Section: Related Workmentioning
confidence: 99%
“…In [37], we proposed an iterative and human-centred knowledge discovery methodology based on FCA. The proposed approach recognises the important role of the domain expert in mining real-world enterprise applications and makes use of specific domain knowledge, including human intelligence and domain-specific constraints.…”
Section: Fca In Criminology: Text Mining Of Police Reportsmentioning
confidence: 99%